Electrocatalysis studies related to [FeFe]-hydrogenase / Woi Pei Meng - Woi, Pei Meng (2011)
This research is concerned with building structures related to the active site of [FeFe] hydrogenase, the H-cluster (a) within surface confined electropolymers (b) in proteins by chemical modification of ferredoxin centres and (c) as catalytic moieties on light harvesting nanoparticles. The study begins by laying out the synthesis of materials used in the studies detailed in this thesis. Components including the cubane cluster, the {2Fe-2S} sub-site centre and the synthesis of functionalised ligands for modification of electrode surfaces and proteins, as well as synthesis of key monomers which can be electropolymerised for electrode surface modification. An improved synthetic route to a key diiron sub-site target molecule is described. Some first steps towards constructing structure related to [FeFe]-hydrogenases on electrode surface are reported. The incorporation of a sub-site unit into an ionic polymer scaffold clearly contributes to the stability of the protonated sub-site, where the presence of the sub-site hydride form is confirmed through infrared spectroscopy. Construction of the active site H-cluster on a modified electrode is described. Electrochemical and spectroscopic characterisations show that a redox active cubane assembly, covalently bound within a cysteinyl-alkylammonium functionalised polypyrrole, can be modified with a diiron dithiolate carbonyl unit to give an artificial hydrogenase H-cluster framework, confined within the polymer matrix. An attempt to construct an H-cluster based on a mutant ferredoxin protein from hyperthermophile Pyroccocus furiosus led to the conclusion that mutant system containing is very robust. It is not easily to unfold it with guanidine hydrochloride, but at low pH, it seems possible that chemistry at one of the iron can be carried out. This is potential very interesting. Preliminary work on constructing a photoelectrochemical platform for hydrogen production is described. This based on the modification of indium phosphide nanocrystals and the incorporation of an Fe2(μ-S2)(CO)6, a procatalyst with a framework nominally related to the catalytic diiron sub-site of hydrogenase. Immobilisation of the components on a gold substrate provides a photocathode which can produce dihydrogen. Finally, a summary of the key findings of this work and an outline of possibilities for future work are provided.